SOCIAL ENTREPRENEURS FINANCIAL FEATURES AND INDICATORS - Martins, Karoline dos Santos (2021)
The paper discus social entrepreneurship financial management, and the broad business market that it covers. The social entrepreneur has different characteristics from other types of entrepreneur in financial resources applications, their results, impacts and considerations both nationally and internationally. The general objective is to show these characteristics of financial applications, and to show its performance in society and in the contemporary economy. The results show the dynamic concepts, and the new forms of entrepreneurship financial management and how business is developed, in the new forms of sustainable development, which is typical of this type of entrepreneurs.